Implementation of the Bina Keluarga Balita Development Program: Efforts to Strengthen Parents' Ability in Caring for Children - Wahyuningsih, Fitri; Wahyuni, Sri; Widianto, Edi (Journal of Nonformal Education, 2020)
The aim of this study is to describe the implementation of Bina Keluarga Balita development program in Klojen Sub-District as an effort to strengthen the ability of parents in childcare. This research uses a quantitative approach with descriptive methods. Data collection is carried out through questionnaires. The respondents in this study amounts 291 participants of Bina Keluarga Balita development program in Klojen Sub-District ofÂ  with a proportional random sampling technique in taking sample members. The analysis of data is used descriptive statistical techniques. The overall results of the study shows that the implementation of Bina Keluarga Balita development program in Klojen Sub-District is very effective as an effort to strengthen the ability of parents in childcare with a percentage of 80,05%. The new finding in this study is that the implementation of Bina Keluarga Balita development program is very effective as an effort to strengthen the ability of parents in childcare which shows that the majority of parents understand the aplication of childcare in early age that suitable with the stages of growth and development. This research provides knowledge to parents as program participants and program implementers to give an overview of the implementation of Bina Keluarga Balita developmentÂ  program.